Examining the Role of Caste and Income in Shaping Adolescents’ Quality of Life - Kumar, Dhrub; Bharti, Aprajita (Journal of Neonatal Surgery, 2025)
This study aimed to explore the independent and joint effects of caste and income on adolescents’ Quality of Life (QoL). Studies were conducted on a sample of 710 adolescents (346 boys, 364 girls) studying in classes X–XII, drawn from the General, OBC, and SC caste categories in the Vaishali District of India. QoL was measured by a 26-item short version of the WHO Quality of Life scale. It measures four domains: physical, psychological, social, and environmental. Results stated that caste differences were largely confined to the environmental domain, with SC adolescents reporting significantly lower scores than General and OBC groups. However, their differences were minimal. Income, on the other hand, significantly influenced all domains of QoL. The higher-income adolescents reported better outcomes, though social relationships were unaffected by income. A two-way ANOVA was computed to measure the main and interaction effects of both income and caste on the quality of life. The findings suggest that income is the more consistent predictor of adolescent QoL. Caste-based inequities were particularly evident in access to environmental resources. The study highlights the need for policy frameworks to resolve structural inequality, ensure equitable resource distribution, and provide targeted support for economically and socially disadvantaged adolescent groups.